Return on Assets, Earnings Per Share, Price Earning Ratio, and Economic Value Added on Stock Returns in The Telecommunications Sub-Industry - Dian Nur Aini; Darto Darto (Dinasti Publisher, 2025)
Rapid economic growth in Indonesia, bolstered by digitization and telecommunications advancements, generates both strategic possibilities and difficulties for the sector, making it crucial to economic expansion and appealing to investors. The purpose of this study is to examine how stock returns in telecommunications sub-industry businesses listed on the Indonesia Stock Exchange for the 2019–2023 timeframe are impacted by Return on Assets (ROA), Earnings Per Share (EPS), Price Earning Ratio (PER), and Economic Value Added (EVA). Purposive sampling is used with panel data regression analysis in this study. Fourteen telecommunications sub-sector businesses that were listed on the IDX between 2019 and 2023 made up the research sample. EViews 10 was used to examine the data. The findings of the research showed that although Price Earning Ratio has a negative and considerable impact on stock returns, Economic Value Added has a negative but negligible impact, and Return on Asset and Earnings Per Share have a positive but negligible impact. The independent variables may account for 32.01% of the variability in stock returns, according to the coefficient of determination (R2) value of 0.320065. The remaining 67.99% is influenced by factors not included in the model.